High CD8+tumor-infiltrating lymphocytes indicate severe exhaustion and poor prognosis in angioimmunoblastic T-cell lymphoma - Zhu, Qiqi; Yang, Yiming; Deng, Xueqin; Chao, Ningning; Chen, Zihang; Ye, Yunxia; Zhang, Wenyan; Liu, Weiping; Zhao, Sha (Frontiers in Immunology, 2023)
Background Exhaustion of CD8+ tumor-infiltrating lymphocytes (TILs), characterized by the overexpression of immune checkpoints (IC), is a major impediment to anti-tumor immunity. However, the exhaustion status of CD8+TILs in angioimmunoblastic T cell lymphoma (AITL) remains unclear. Therefore, we aimed to elucidate the exhaustion status of CD8+TILs in AITL and its influence on prognosis. Methods The correlation between CD8+TILs and IC expression in AITL was analyzed using single-cell RNA sequencing (n = 2), flow cytometry (n = 20), and RNA sequencing (n = 20). Biological changes related to CD8+TILs exhaustion at different cytotoxic T lymphocyte (CTL) levels (mean expression levels of CD8A, CD8B, GZMA, GZMB, and PRF1) in AITL were evaluated using RNA sequencing (n = 20) and further validated using the GEO dataset (n = 51). The impact of CD8 protein expression and CTL levels on patient prognosis was analyzed using flow cytometry and RNA sequencing, respectively. Results Our findings demonstrated that the higher the infiltration of CD8+TILs, the higher was the proportion of exhausted CD8+TILs characterized by the overexpression of multiple IC. This was accompanied by extensive exhaustion-related biological changes, which suggested severe exhaustion in CD8+TILs and may be one of the main reasons for the poor prognosis of patients with high CD8+TILs and CTL. Conclusion Our study comprehensively reveals the exhaustion status of CD8+TILs and their potential negative impact on AITL prognosis, which facilitates further mechanistic studies and is valuable for guiding immunotherapy strategies.